Thoracoscopic surgery under epidural anesthesia for secondary spontaneous pneumothorax - Salman Ahmed; Muhammad Hassan Raza; Shafia Safdar; Muhammad Umair Ashraf; Khalil Ahmed; Sardar Saud Abbas (Medical Journal of South Punjab, 2024)
Objective: The aim of the study was to compare the outcomes of thoracoscopic surgery for spontaneous pneumothorax when performed under epidural local anesthesia (ELA) versus under general anesthesia. Methodology: Prospective study was conducted at LUMHS Jamshoro, Pakistan over a 2-year period from 2019 to 2021, involving 180 patients who were randomly assigned using a computer-generated random number table. Patients aged 21–65 with ASA I and II classifications, diagnosed with pleural pathologies and scheduled for VATS procedures, were included in the study, with a restriction to a two-hour time limit. Results: According to pulmonary lung functions, the mean FEV1/FVC, DLCO and preoperative dyspnea score based on ATS was less in EA patients than GA patients, (p<0.001). Whereas, underlying lung disease, COPD and ILD of GA and EA patients were almost equal, (p>0.050). The mean operative time in GA and EA patients was 110.12±13.92 minutes and 104.58±7.86 minutes, respectively, (p=0.023). Conclusion: ELA exhibits advantages in terms of shorter global operating room time and a reduced incidence of related complications, highlighting its potential as a preferred approach for this procedure.